Big Family, No Maid, Tight Budget! - Dow Chemical Company (1957)
Color print advertisement for Saran Wrap, a product of the Dow Chemical Company. The advertisement profiles the Read family of Ridgewood, New Jersey and features photographic reproductions of various cookies and party treats wrapped in Saran Wrap to lock in freshness and moisture. Initially developed for the U.S. Army to wrap arms and equipment for transport during World War II, saran plastic was subsequently developed and marketed as Saran Wrap for household use.
Keywords: Plastics; Chemical industry; Dow Chemical Company; Teenagers; Women in advertising; Advertising; Children; Plastics industry and trade; Corporations